Effects of spacing and nitrogen levels on yield and yield contributing characters of maize - Rahman, MM; Paul, SK; Rahman, MM (Journal of the Bangladesh Agricultural University, 2016)
An experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh during November 2014 to April 2015 to investigate the effect of planting spacing and nitrogen levels on yield attributes and yield of maize cv. Khaibhutta. The experiment comprised three nitrogen levels viz. 50, 100 and 150 kg N ha-1 and five plant spacings viz. 75 cm × 25 cm, 75 cm × 20 cm, 50 cm × 25 cm, 50 cm × 20 cm and 100 cm × 20 cm. The experiment was laid out in a randomized complete block design with three replications. Results revealed that nitrogen levels and plant spacing had significant effect on yield attributes and yield of Khaibhutta. The highest number of cobs plant-1, grains row-1, grain yield and stover yield were recorded with 150 kg N ha-1 followed by 100 kg N ha- 1and the lowest values were observed in 50 kg N ha-1. The highest number of cobs plant-1, grain rows cob-1, grains row-1, grains cob-1, 1000-grain weight, grain yield and harvest index were recorded at 75 cm × 25 cm spacing. In contrast, the closest spacing of 50 cm x 20 cm produced the lowest values of grain rows cob-1, grains row-1, grains cob-1, 1000-grain weight and grain yield. In case of interaction, the highest grain yield and harvest index were obtained at 75 cm × 25 cm spacing fertilized with 150 kg N ha-1. The lowest values of the above parameters were recorded in the closest spacing 50 cm × 20 cm with 50 kg N ha-1. From this study it may be concluded that maize (cv. Khaibhutta) can be cultivated at the spacing of 75 cm × 25 cm with 150 kg N ha-1 for appreciable grain yield. J. Bangladesh Agril. Univ. 14(1): 43-48, June 2016